Genome-wide association and genomic prediction identifies soybean cyst nematode resistance in common bean including a syntenic region to soybean Rhg1 locus. Issue 1 (1st January 2019) - Wen, Liwei; Chang, Hao-Xun; Brown, Patrick J; Domier, Leslie L; Hartman, Glen L
Abstract: A genome-wide association study (GWAS) was applied to detect single nucleotide polymorphisms (SNPs) significantly associated with resistance to Heterodera glycines (HG) also known as the soybean cyst nematode (SCN) in the core collection of common bean, Phaseolus vulgaris . There were 84, 416 SNPs identified in 363 common bean accessions. GWAS identified SNPs on chromosome (Chr) 1 that were significantly associated with resistance to HG type 2.5.7. These SNPs were in linkage disequilibrium with a gene cluster orthologous to the three genes at the Rhg1 locus in soybean. A novel signal on Chr 7 was detected and associated with resistance to HG type 1.2.3.5.6.7. Genomic predictions (GPs) for resistance to these two SCN HG types in common bean achieved prediction accuracy of 0.52 and 0.41, respectively. Our study generated a high-quality SNP panel for 363 common bean accessions and demonstrated that both GWAS and GP were effective strategies to understand the genetic architecture of SCN resistance in common bean. Winning the war against worms: A broad genomic mapping effort in the common bean reveals sequence elements that may help protect this crop from plant-killing worms. The soybean cyst nematode has the potential to wreak havoc on the common bean, an important food source in many countries. Researchers led by Glen Hartman at the US Department of Agriculture conducted an extensive survey of 363 different derivatives of this crop in order to identify genetic features that might confer resistance against two different strains of this infectious worm. Their study identified regions on three different chromosomes that each appear to contribute some degree of protection against soybean cyst nematode. These offer starting points for understanding the molecular foundations of pest resistance in this crop, and could facilitate the future breeding of more robust bean strains.